1998
DOI: 10.1002/(sici)1096-9861(19980222)391:4<506::aid-cne7>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Nigrothalamic projections and nigrothalamocortical pathway to the medial agranular cortex in the rat: Single- and double-labeling light and electron microscopic studies

Abstract: Although the rat medial agranular cortex (AGm) has been implicated in a variety of motor functions, the source of the afferents impinging upon thalamic neurons projecting to the AGm is not directly known. The main purpose of this study was to determine whether the AGm is a major recipient of the nigrothalamocortical pathway. This issue was addressed by two sets of experiments. First, the organization of the nigrothalamic projections was studied by light and electron microscopy following injections of the anter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 78 publications
(164 reference statements)
7
38
0
Order By: Relevance
“…No significant differences were found between the ultrastructural characteristics of nigral and pallidal axon terminals, and both displayed a common pattern of synaptic innervation of their targets (Grofová and Rinvik, 1974;Kultas-Ilinsky et al, 1983;Kultas-Ilinsky and Ilinsky, 1990;Sidibé et al, 1997). These studies have shown that the main postsynaptic target of the afferent fibers are the postsynaptic dendrites of relay cells (Grofová and Rinvik, 1974;Kultas-Ilinsky et al, 1983;Kultas-Ilinsky and Ilinsky, 1990;Sidibé et al, 1997) or identified thalamocortical neurons (Kayahara and Nakano, 1996;Sakai et al, 1998).…”
Section: The Output Organization Of the Basal Ganglia To The Thalamusmentioning
confidence: 84%
See 3 more Smart Citations
“…No significant differences were found between the ultrastructural characteristics of nigral and pallidal axon terminals, and both displayed a common pattern of synaptic innervation of their targets (Grofová and Rinvik, 1974;Kultas-Ilinsky et al, 1983;Kultas-Ilinsky and Ilinsky, 1990;Sidibé et al, 1997). These studies have shown that the main postsynaptic target of the afferent fibers are the postsynaptic dendrites of relay cells (Grofová and Rinvik, 1974;Kultas-Ilinsky et al, 1983;Kultas-Ilinsky and Ilinsky, 1990;Sidibé et al, 1997) or identified thalamocortical neurons (Kayahara and Nakano, 1996;Sakai et al, 1998).…”
Section: The Output Organization Of the Basal Ganglia To The Thalamusmentioning
confidence: 84%
“…3A with Fig. 3 from Sakai et al, 1998), and also in the rostral intralaminar and mediodorsal nuclei, where even a complementary pattern is hinted (see Fig. 3A-A%, B-B%; for methodological considerations see Lanciego et al, 1998).…”
Section: The Output Organization Of the Basal Ganglia To The Thalamusmentioning
confidence: 85%
See 2 more Smart Citations
“…In this respect, there is evidence for the inhibition of hippocampal acethylcholine release by cannabinoids . Moreover, metabolic depression was measured in the ventromedial thalamic nucleus that has been implicated in arousal mechanisms (Sakai et al 1998).…”
Section: Discussionmentioning
confidence: 99%